Youtefa Bay: Dealing with Pollution Threats and Ecosystem Conservation - Apner Krei (Formosa Journal of Social Sciences (FJSS), 2024)
This study examines the sources and impacts of marine pollution in Youtefa Bay, Papua, Indonesia, and proposes mitigation strategies. Primary pollution sources include domestic waste, plastic debris, industrial effluents, oil spills, and agricultural runoff causing eutrophication. The research employs qualitative methods, including literature review, interviews, and field observations. Findings indicate significant ecological damage, loss of biodiversity, and socio-economic impacts on local communities. The study recommends a multifaceted approach to pollution management, emphasizing improved waste infrastructure, stricter regulations, community engagement, and eco-tourism development